Assembleia de pequenos mamíferos em uma região de cerrado no norte de Minas Gerais - Carvalho, Éder Costa (2016)
The use and degradation of natural environments for human activities is currently the main threat to global biodiversity. The Brazilian Cerrado has a high diversity and a high degree of endemism. However, a small part of its natural area remains unaltered, which makes the biome be included among the hotspots of global biodiversity conservation. It becomes important, for the conservation of biodiversity, to understand the response of plant and animal communities face to environmental changes and human activities. Here we discuss the responses of a small mammals community in a Cerrado region with different levels of human presence and analyze some environmental variables that can influence in the richness and abundance of this community. In order to accomplish this, we captured small mammals in eight points. Of those, four were captured in an area with less human presence and four were captured in an area with greater human presence. We recorded 10 species of small mammals. The composition and structure analysis of community did not show differences between the two areas. The high presence of generalist species and the high relative abundance of Gracilinanus agilis explain this similarity between the communities of these two areas. The heterogeneity of habitat was important to explain the variety of small mammals in the region. In places with presence of veredas or dry forests, the variety of small mammals was higher. The abundance of small mammals community was influenced by the presence of cattle. In a certain degree, the abundance of small mammals seems to support the effects of the presence of pets. However, with the increase of the its abundance, small mammals begin to decrease their abundance. The preservation of all kinds of vegetation existing in the Cerrado is important for the preservation of a greater diversity of small mammals. As the creation of loose cattle is a commonplace activity in the region and it affects the small mammal community, inspection actions on this activity become important for the conservation of these animals.